2017
DOI: 10.1002/ece3.3242
|View full text |Cite
|
Sign up to set email alerts
|

Using digital soil maps to infer edaphic affinities of plant species in Amazonia: Problems and prospects

Abstract: Amazonia combines semi‐continental size with difficult access, so both current ranges of species and their ability to cope with environmental change have to be inferred from sparse field data. Although efficient techniques for modeling species distributions on the basis of a small number of species occurrences exist, their success depends on the availability of relevant environmental data layers. Soil data are important in this context, because soil properties have been found to determine plant occurrence patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…There are soil maps at a nominal 1‐km spatial resolution, but they have been found to contain major inaccuracies (Moulatlet et al . ). Topography is also related to hydrology and sedimentation (Wittmann et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There are soil maps at a nominal 1‐km spatial resolution, but they have been found to contain major inaccuracies (Moulatlet et al . ). Topography is also related to hydrology and sedimentation (Wittmann et al .…”
Section: Discussionmentioning
confidence: 97%
“…Soils are a relevant factor for SDM (Figueiredo et al 2018), but accurate enough soil data are not available for our study area. There are soil maps at a nominal 1-km spatial resolution, but they have been found to contain major inaccuracies (Moulatlet et al 2017). Topography is also related to hydrology and sedimentation (Wittmann et al 2004), including the difference between inundated and terra firme forests.…”
Section: Discussionmentioning
confidence: 99%
“…However, when soil properties have not been measured at the site but their impact needs to be inferred from soil type data derived from digital soil maps, their direct impact is not easy to quantify. This is partly due to accuracy problems and georeferencing errors in the available digital soil data, which themselves have been derived from scant field data (Moulatlet et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although digital soil maps exist (Hengl et al, 2017), they do not provide layers of soil base cation concentration. The digitally available variables, such as soil type and cation exchange capacity have had only weak relationships with field-measured base cation concentration (Moulatlet et al, 2017). Therefore, we used Landsat imagery as a surrogate, since earlier studies at the landscape extent have found them useful for identifying spatial heterogeneity in soils and soil-related floristic patterns (Higgins et al, 2012(Higgins et al, , 2011Salovaara et al, 2005;Tuomisto, Poulsen, et al, 2003;Tuomisto, Ruokolainen, Aguilar, et al, 2003).…”
Section: Floristic Environmental and Remotely Sensed Datamentioning
confidence: 99%